2018
DOI: 10.2134/jeq2018.01.0037
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Leaching from an Organic and a Mineral Arable Soil in a Rainfall Simulation Study

Abstract: Phosphorus derived from agricultural systems has been found to cause eutrophication of surface waters. To combat this, the specific location of soil profile P release is necessary for development of effective mitigation strategies. This paper describes a P leaching study of two Swedish arable soils, an organic (Typic Haplosaprist) and a mineral soil (Typic Hapludalf), both with high P content. Undisturbed soil columns isolated 0- to 20-, 20- to 40-, 40- to 60-, and 60- to 80-cm depth intervals. These were plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 65 publications
2
10
1
Order By: Relevance
“…For most soil cores from the drained site, a high phosphate concentration (approximately 2 mg P l −1 ; Figure ) was observed in the leachate. The high P leaching concentrations are in consistent with recent studies by Parvage, Ulén, & Kirchmann () and Riddle et al (), who observed a range of phosphate concentrations in the effluent from 0.36 to 10.3 mg P l −1 for organic soils. For the studied fen peat, the redox sensitive P accounts for only <4% of total P, which is a small fraction if compared to values reported in other studies (>15%; Forsmann & Kjaergaard, ).…”
Section: Resultssupporting
confidence: 91%
“…For most soil cores from the drained site, a high phosphate concentration (approximately 2 mg P l −1 ; Figure ) was observed in the leachate. The high P leaching concentrations are in consistent with recent studies by Parvage, Ulén, & Kirchmann () and Riddle et al (), who observed a range of phosphate concentrations in the effluent from 0.36 to 10.3 mg P l −1 for organic soils. For the studied fen peat, the redox sensitive P accounts for only <4% of total P, which is a small fraction if compared to values reported in other studies (>15%; Forsmann & Kjaergaard, ).…”
Section: Resultssupporting
confidence: 91%
“…The lower concentration of plant available P at the subsurface than surface horizons and lack of significant differences at the subsurface horizons indicated that P translocation from the surface to the subsurface horizons was negligible or the leached P lost from the soil profiles. Other researchers reported the danger of P leaching from the surface to subsurface horizons of peat soils upon rewetting [14,40]. The disagreeing results can be attributed to variations in current land use, soil organic matter content, and predominant P species or experimental approaches, and peatland types.…”
Section: Total Elements and Plant Available Phosphorusmentioning
confidence: 98%
“…Many previous studies reported that rewetting increased P solubility and mobility in soils [13,14,40]. These studies, however, investigated the effect of anaerobic conditions on degraded fen peat that was previously P-enriched by fertilization.…”
Section: Synthesismentioning
confidence: 99%
“…Nonpoint‐source pollution based on rural and agricultural organic matter receives less attention than pollution caused by point sources such as domestic sewage and industrial wastewater and from nutrients such as nitrogen and phosphorus (Sun et al, 2016; Riddle et al, 2018). Rivers in rural and agriculture‐dominated watersheds collect various pollutants, especially organic matter, from diverse sources.…”
Section: Resultsmentioning
confidence: 99%